Market Integration in the Philippine Milkfish Industry - D. Salayo, Nerissa (1989)

(untitled)
Sufficiency in milkfish production in the Philippines was mainly attributed to the improved production technologies. However, sufficiency in food does not come from production increases alone. Efficiency in marketing should be attained to guarantee an adequate supply of milkfish in consumption areas at equilibrium price. An efficiently integrated market is characterized by prices that are interrelated. The study focuses on the analysis of milkfish prices from 1978 to 1987 with the end view of assessing the degree of integration between Metro Manila and selected regional production centres. Ravallion's autoregressive distributed lag model (1986) and cross-correlation of residuals by Box and Pierce ( 1970) revealed that the Philippine milkfish market is not well integrated. The hypotheses of long-run integration and the absence of local market characteristics were accepted while short-run integration and segmentation were rejected. Hence, the process of price adjustment in the regional market do not fully reflect the price information from the reference market within a short time period but equilibrium could be attained in the long-run. Price formation runs from the wholesale to the retail market and furthermore from the reference market to the regional production centres. The low levels of integration are often associated with margins in excess of the marketing costs since arbitragers could use information about price differences profitably. Non-economic profits exist in markets laden with structural imperfections. Hence, the need for the government's attention to save the declining profitability of milkfish production juxtaposed with the enrichment of influential intermediaries in the face of increasing productivity.